Pengaruh Karakteristik Perusahaan Dan Corporate Governance Terhadap Praktik Pengungkapan Sustainaibility Report (Studi Empiris Pada Perusahaan Manufaktur Yang Tercatat Di Bursa Efek Indonesia 2012-2014) - Iswari, Agnes Maulidya; , Dr. Fatchan Achyani, S.E, M.Si (2016)
The purpose of this study is to analyzed the effect of the characteristic of the company and corporate governance disclosure to sustainability report. Characteristic of the company used in research is profitability ROA, company size, and company activity. For corporate governance used in research is audit committee, board of directors, governance committee, and independent commisaris. Population of this study were taken from manufacture company listed on indonesia stock exchangeobservation period of 2012-2014. This study uses purposive sampling method and collected 37 samples. Data analysis whit test clasic assumption and hypoteses test method used multiple regression. The result show characteristic of the company that company size significantinfluence to the disclosure of sustainability report. In corporate governance that governance committee significan influence to the disclosure of sustainability report.